The parliamentary roots of European social policy : turning talk into power - Roos, Mechthild (Palgrave studies in European Union politics, 2021)
The European Parliament (EP) a powerful actor in today's European Union was not intended to be more than a consultative assembly at first. Yet this book shows that the EP was much more influential in shaping Community policy in the early years of the integration process than either the founding Treaties or most existing scholarship would allow. It studies the EPs institutional evolution through the lens of Community social policy, a policy area with a particularly strong ideational dimension. By promoting a European social dimension, Members of the EP (MEPs) presented the Parliament as the true representative of European citizens by channelling their interests and needs. MEPs thus emphasised the EPs role as a provider of democratic legitimacy for Community politics, whilst at the same time trying to convince European citizens that the Communities could have a real and positive impact on their everyday lives. Mechthild Roos is Lecturer in Comparative Politics, Augsburg University, Germany.